Cinética de parâmetros metabólicos e inflamatórios no fígado de camundongos alimentados com dieta rica em carboidratos refinados - Marina Chaves de Oliveira (2013)
Obesity is characterized by adipose tissue expansion as well as metabolic and inflammatory dysfunction. Liver diseases are part of the associated comorbidities related to obesity. The aim of this study was to evaluate the kinetics of metabolic and inflammatory liver dysfunction induced by high refined carbohydrate-containing diet (HC) in mice. BALB/c mice were fed a chow or HC diet in the following experimentalperiods: 1 and 3 days, 1, 2, 4, 6, 8, 10 and 12 weeks. The animals fed HC diet presented hypertriglyceridemia and hypercholesterolemia without changes in transaminases ALT and AST. It was observed higher level content of total cholesterol and triglyceride in animals fed HC diet in all experimental periods. The expression of mRNA for the genes of ChREBP, SREBP-1 and SREBP-2 was performed by realtime PCR. No alterations were observed in these transcription factors in the animalsfed HC diet. In the morphological analysis evaluated with H&E and Gomori's trichrome staining, mice fed HC diet presented higher hyperemia, steatosis, inflammatory infiltrate and perivascular inflammation. It was also observed a transient increase in the area of deposited collagen. In separated experiment, intravital microscopy was performed in Lysm-eGFP mice to evaluate the neutrophil infiltration in the liver. Animals fed HC diet for 3 days, 8 and 12 weeks showed higher number of circulating neutrophils in hepatic sinusoids. The content of TNF- and IL-10 was higher in the beginning of the experimental period while it was lower from the 8th week of consumption of HC diet compared to controls. The concentration of IL-6 was also lower from the 8th week of consumption of HC diet. The cytokines IL-13 and IL-4 presented higher levels from the 6th week of diet and remained high until the end of experimental period. The present work suggests that consumption of a high refined carbohydrate-containing diet induces liver dysfunction including fat deposition, infiltration of inflammatory cells, such as neutrophils, and altered cytokine profile. As a result, the liver showed morphological changes and collagen deposition in hepatocytes.